Actividad catalítica de ceniza de cáscara de Theobroma bicolor Bonpl. para transesterificar aceite vegetal usado – Iquitos 2023 - Dávila Ríos, Gonzalo (2024)
This study investigated the usefulness of macambo fruit shell ash (Theobroma bicolor Bonpl.) as a catalyst in the conversion of used vegetable oils (UVO) into biodiesel. The UVO was characterized, and the catalyst was prepared by calcination at 700°C, evaluating its basic strength and potassium and calcium content. Using a 23 factorial experimental design, three critical factors were investigated at two levels: molar ratio of methanol/oil (MR: 6/1 and 9/1), reaction time (RT: 60 and 90 minutes), and catalyst amount (CC: 2% and 3%). It was found that the UVO had 0.61% moisture and an acidity index of 0.28 (mg of KOH/g oil), suitable for direct transesterification. The catalyst showed a yield of 0.91%, with high potassium (38.40%) and calcium (1.76%) contents, and maximum basicity at pKBH= 9.8, indicating its catalytic efficacy. Transesterification assays revealed average biodiesel yields between 84.97% and 92.64%, with statistical significance (p < 0.05). The best biodiesel yield conditions were MR of 6/1, RT of 60 minutes, and CC of 3%. These findings support the viability of using macambo shell ash as an effective catalyst to produce biodiesel from UVO.